Application of Standardized Rosa damascena Stem Cell-Derived Exosomes in Dermatological Wound Healing and Scar Management: A Retrospective Case-Series Study with Long-Term Outcome Assessment - Lidia Majewska; Agnieszka Kondraciuk; Karolina Dorosz; Agnieszka Budzyńska (Pharmaceutics, 2025)
Background: Scar formation and impaired wound healing represent significant challenges in dermatology and aesthetic medicine, with limited effective treatment options currently available. Objectives: To evaluate the efficacy and long-term outcomes of Damask rose stem-cell-derived exosome (RSCE) therapy in the management of diverse dermatological conditions, including traumatic wounds, surgical scars, and atrophic acne scars. Methods: We conducted a case series study from June 2023 to November 2024, documenting four cases with different types of skin damage treated with lyophilized RSCE products. Treatment protocols included a variety of delivery methods such as topical application, microneedling, and post-procedure care. Follow-up assessments were performed at intervals ranging from 7 days to 10 months. Results: All patients demonstrated significant improvements in scar appearance, skin elasticity, hydration, and overall tissue quality. In traumatic facial injury, RSCE therapy facilitated reduction in scar contracture and improved functional outcomes. For atrophic acne scars, comparative treatment of facial sides showed enhanced results with RSCE addition. Acute wounds exhibited accelerated healing with reduced inflammation, while chronic wounds demonstrated improved epithelialization and long-term scar quality. Conclusions: This case series provides preliminary evidence suggesting that RSCE therapy may offer significant benefits in wound healing and scar management. The observed improvements in tissue regeneration, inflammatory modulation, and long-term aesthetic outcomes warrant further investigation through controlled clinical trials.